The Lysine Demethylase KDM7A Regulates Immediate Early Genes in Neurons - Yifan Wang; Qin Hong; Yueyue Xia; Zhao Zhang; Bo Wen (Advanced Science, 2023)
Abstract Lysine demethylase KDM7A removes histone modifications H3K9me1/2 and H3K27me1/2. KDM7A plays critical roles in gene expression and contribute to biological processes including tumorigenesis, metabolism, and embryonic development. However, the functions of KDM7A in mammalian nervous system are still poorly explored. In this study, functional roles of KDM7A are comprehensively investigated in neuronal cells by applying CUT&Tag‐seq, RNA‐seq and mice models. Knockdown of Kdm7a in N2A cells result in the alteration of histone modifications near transcription start sites (TSSs) and the expression changes of a large number of genes. In particular, the expression of immediate early genes (IEGs), a series of genes maintaining the function of the nervous system and associating with neurological disorders, are significantly decreased upon Kdm7a knockdown. Furthermore, in vivo knockdown of Kdm7a in dentate gyrus (DG) neuron of mice hippocampus, via Adeno‐associated virus (AAV)‐based stereotaxic microinjection, led to a significant decrease of the expression of c‐Fos, a marker of neuron activity. Behavior assays in mice further revealed that Kdm7a knockdown in hippocampus repress neuron activity, which leading to impairment of emotion and memory. Collectively, the study reveals that KDM7A affects neuron functions by regulating IEGs, which may provide new clues for understanding epigenetic mechanisms in neurological disorders.